Contours of a research ethics and integrity perspective on open science - Lindemann, Tom; Häberlein, Lisa (Frontiers in Research Metrics and Analytics, 2023)
This article argues that adopting a research ethics and integrity perspective could support researchers in operationalizing the open science guiding principle “as open as possible, as closed as necessary” in a responsible and context-sensitive manner. To that end, the article points out why the guiding principle as such provides only a limited extent of action-guidance and outlines the practical value of ethical reflection when it comes to translating open science into responsible research practice. The article illustrates how research ethics and integrity considerations may help researchers understand the ethical rationale underpinning open science as well as recognize that limiting openness is necessary or at least normatively permissible in some situations. Finally, the article briefly discusses possible consequences of integrating open science into a responsibility-centered framework and implications on research assessment.